Preparedness of Society to Confront of Forest Fire and Peatland in Singkawang City - Wulandari, Fajar; Yanti, Lili (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This research studies analyzing the community and students in Singkawang City that have an impact on forest fires on peatlands, fire attacks because it increases the dry season that triggers forest fires so it is felt, this research was conducted to prevent dangerous material. Data was collected using a questionnaire method, through this questionnaire will be discussed the level of preparedness to deal with forest fires in the City of Singkawang. The method used in this research is descriptive quantitative. Quantitative samples using purposive random sampling techniques. The subject will be used as a sample of research in Singkawang City community and high school students in Singkawang City. The data to be obtained in this study will be published by descriptive by describing the results of the research obtained from the research questionnaire and then the data obtained will be classified by techniques that can compare each person so that from the groups that can be done this can be done to improve disaster fire preparedness.